SOCIO-ECONOMIC FACTORS OF CIVIL SOCIETY DEVELOPMENT IN THE CONDITIONS OF MODERN CHALLENGES - Sapych, Vadym (European Science, 2025)
The effective use of human resources during the war is largely determined by the active civic position of people, their responsibility and cohesion. The paper shows the analysis of the following socio-economic factors of civil society development in Ukrai